Uncommon functional properties of the first piscine 26S proteasome from the Antarctic notothenioid Trematomus bernacchii. Issue 2 (15th April 2016) - Gogliettino, Marta; Balestrieri, Marco; Riccio, Alessia; Facchiano, Angelo; Fusco, Carmela; Palazzo, Vincenzo Cecere; Rossi, Mosè; Cocca, Ennio; Palmieri, Gianna
Abstract : The antioxidant defense mechanisms have a great impact on the life of Antarctic organisms. The present study could represent the first evidence of a direct involvement of the 26S proteasome in the antioxidant defense systems of fish adapted to cold. Abstract : Protein homoeostasis is a fundamental process allowing the preservation of functional proteins and it has a great impact on the life of the Antarctic organisms. However, the effect of low temperatures on protein turnover is poorly understood and the cold-adaptation of the degradation machinery remains an unresolved issue. As the 26S proteasome represents the main proteolytic system devoted to the controlled degradation of intracellular proteins, the purpose of the present study was to investigate the functions of this complex in the notothenioid Trematomus bernacchii, in order to better understand its role in the physiology of Antarctic fish. To this aim, we purified and characterized the 26S proteasome from T. bernacchii and isolated the cDNAs codifying seven of the 14 subunits belonging to the proteasome 20S core particle. Results provided evidences of the high resistance of the piscine 26S proteasome to oxidative agents and of its 'uncommon' ability to efficiently hydrolyse oxidized bovine serum albumin (BSA), suggesting that this enzymatic complex could play a key role in the antioxidant defense systems in fish inhabiting permanently cold marine environments. These unique properties were also reflected by the 3D model analysis, which revealed a higher structural stability of the piscine complex respect to the murine template. Finally, a comparative analysis, performed in a variety of tissues collected from T. bernacchii and the temperate fish Dicentrarchus labrax, showed a lower protein retention in the cold-adapted fish, possibly due to a better efficiency of its degradation machinery.